KETEBALAN LEMAK SUBKUTAN DENGAN KADAR HDL DAN LDL PADA MAHASISWI OVERWEIGHT DI PESANTREN: Pengaruh Ketebalan Lemak Subkutan terhadap Kadar HDL Dan LDL Mahasiswi Overweight Di Universitas Berbasis Pesantren - Damayanti, Amilia Yuni; Fatimah, Fatimah; Luthfiya, Lulu'; Kusumadiastuti, Afina Deni (Amerta Nutrition, 2023)
Background: Indonesia is now facing overweight problem as one of the major nutritional problems. It occurs due to excessive fat in the body. The distribution of body fat from subcutaneous fat can increase health risks such as dyslipidemia, one of which is characterized by abnormal High-Density Lipoprotein (HDL) and Low-Density Lipoprotein (LDL) levels. Objectives: The purpose of this study was to analyze the relationship between subcutaneous fat thickness and HDL LDL levels in overweight students at Universitas Darussalam Gontor. Methods: This study used a cross-sectional design. The research subjects were 50 overweight adult women aged 18-25 years using the Lemeshow formula selected using consecutive sampling while the data analysis using the Chi-Square test. Data taken includes body fat percentage from measuring the thickness of subcutaneous fat folds using a skinfold caliper measuring instrument, and checking the lipid profile from HDL and LDL levels. Results: The average thickness of subcutaneous fat in overweight female students was 32% body fat with high category (64%). The average HDL level was classified as normal (70%), while the LDL level was classified as high (58%).  The results of the analysis test on the relation between subcutaneous fat thickness and HDL levels showed no significant difference with HDL levels (p-value = 0.199 [>0.05]). While there is a significant relationship between the subcutaneous fat thickness and LDL levels with a p-value of 0.042 (<0.05). Conclusions: There is no significant relationship between subcutaneous fat thickness and HDL level contrarily, there is a relationship between subcutaneous fat thickness and LDL levels. Monitoring the thickness of subcutaneous fat needs to be done as a form of controlling LDL levels.